Injury Prevention and Treatment among Elderly Individuals in the Sukoharjo Village’s Posyandu Lansia Sehat Bugar - Leni, Ari Sapti Mei; Widarti, Rini; Sari, Irma Mustika; Noorrarti, Erika Dewi (Universitas Muhammadiyah Surakarta, 2023)
The household environment is vulnerable to domestic accidents, underscoring the necessity of possessing fundamental expertise in first aid as the primary approach to addressing such incidents before subsequent medical interventions. Insufficient attention to this primary measure can result in more severe injuries. Notably, a deficiency exists in targeted interventions that aim to enhance the elderly population's comprehension of strategies to prevent and treat domestic accidents. Two approaches have been implemented to tackle this issue and augment the elderly population's understanding. These methods encompass educational lectures and practical demonstrations tailored to seniors, specifically focusing on preventing and treating domestic accidents. As a result, there is observable enhancement in knowledge after the provision of information through community health education initiatives. Preceding the dissemination of insights into injury prevention and treatment among the elderly, knowledge distribution is categorized: 11% categorized as 'good,' reflecting a high level of knowledge; 33% as ‘moderate,' indicating a sufficient level; and 56% as 'poor,' representing a lower level of knowledge. A noticeable increase is observed upon sharing the information, with 61% rise in 'good' categories, a corresponding 39% increase of 'moderate' categories, while the 'poor' category remains unchanged. The findings indicate increased understanding among the elderly concerning injury prevention and treatment of domestic accidents.